Meningkatkan Hasil Belajar Siswa dalam Pembelajaran PAKBP dengan Metode Problem Based Learning (PBL) dengan Bantuan Media Audio Visual pada Kelas IV Fase B di SD Negeri 101808 Candirejo Tahun Pembelajaran 2024/2025 - Eva Santa Rosa Sitanggang (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This Class Action Research aims to improve student learning outcomes in the subject of Catholic Religious Education and Ethics (PAKBP) through the Problem-Based Learning (PBL) method with audio-visual media on the material "I Am a Unique Person." The subjects of the study were five fourth grade students of SD Negeri 101808 Candirejo, which showed low learning outcomes in this material. The research was carried out in two cycles, each through the stages of planning, implementation, observation, and reflection. In Cycle I, the average grade of the class increased from 65.4 to 71.8, but did not meet the success criteria. After improvements in Cycle II, including improvements in the quality of media and facilitation, learning outcomes improved with an average class score of 82.8 and 100% learning completion. PBL and audio-visual media have proven to be effective in strengthening the understanding and internalization of the value of self-uniqueness. Recommendations include expanding PBL implementation, media development, teacher training, follow-up research, and collaboration with parents and the church community.